Analisis Penggunaan Akun Instagram @Melekteknologi.Id Dalam Memenuhi Kebutuhan Informasi Mahasiswa Ilmu Perpustakaan Stambuk 2018 - Ritonga, Sahpriani; Rohani, Laila; Yusniah, Yusniah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to determine the use of Instagram accounts in meeting the information needs of library science students and to find out the obstacles experienced by library science students. The method used in this study is a qualitative method with a descriptive approach that uses interviews to describe the data obtained by researchers directly, to obtain a clear and detailed picture of how the use of the @melektechnology.id Instagram account is to fulfill the information needs of 2018 Stambuk Library Science students. Data collection techniques used in this study were observation, interviews and documentation. Furthermore, the researchers conducted interviews with informants who follow the @melektechnology.id Instagram account. The results of this study indicate that the informants who have been interviewed all follow the @melektechnology.id instagram account and they take advantage of the information contained in the account according to the needs they want. Constraints experienced by informants when searching for information on the account, namely an unstable network, cellular data and information on the account drowned. Keywords: Information needs, Instagram